COVID-19 among Nursing Staff: Settings and Regional Differences - Hoedl,Manuela (2021)
Abstract Background/Aims: So far detailed insights into the nursing staff’s COVID-19 symptoms, testing, and results are missing. Therefore, this study aimed to describe the setting and regional differences in the occurrence of COVID-19 among nursing staff, analysing symptoms, testing, and their respective results. Methods: We used an online survey to conduct this cross-sectional study among Austrian nursing staff in different settings between May 12 and July 13, 2020. This article follows the STROBE statement. The survey includes demographic data, including age, professional qualification, e.g., nurse, nurse aid, and in which federal state and setting the participants work. In addition, we asked for COVID-19 symptoms and (result of the) testing. We used descriptive statistics as well as bivariate analysis to calculate the differences. Results: Nearly every sixth nurse reported experiencing COVID-19 symptoms. We found statistically significant differences between the settings and the federal provinces for the reported COVID-19 symptoms, but not the test results. In total, 1.6% of the participating nurses were tested for COVID-19, of which all were positive for COVID-19. Conclusions: In the future during a pandemic, health care staff should be comprehensively tested in all settings. Our results showed that shifting the perspectives from critical/acute settings to other settings, such as nursing homes, is needed.